Time-Specific Associations of Tumor Necrosis Factor-α Levels and Polymorphisms (−850 C/T or −308 G/A) With Suicidal Ideation in Acute Coronary Syndrome Patients - Kang, Hee-Ju; Kim, Ju-Wan; Lee, Ju-Yeon; Kim, Sung-Wan; Shin, Il-Seon; Hong, Young Joon; Ahn, Youngkeun; Jeong, Myung-Ho; Kim, Jae-Min (Frontiers in Psychiatry, 2021)
Background: Considering association of inflammation with suicide and acute coronary syndrome (ACS), we investigated the individual and interactive effects of serum tumor necrosis factor-alpha (sTNFα) levels and two polymorphisms (−850 C/T or −308 G/A) on suicidal ideation (SI) after ACS. Methods: The SI status using items on the Montgomery–Åsberg Depression Rating Scale, related covariates including socio-demographic and clinical characteristics, sTNFα levels and TNF-α polymorphisms were evaluated in 969 patients within 2 weeks after ACS. Of the patients, 711 were evaluated 1 year later for SI. Multivariate logistic regression models were used to calculate individual and interactive associations after adjusting for the covariates. Results: Higher (vs. lower) sTNFα levels and the –850 C/T or T/T (vs. C/C) polymorphism were significantly associated with SI 2 weeks after ACS, while only higher sTNFα levels were significantly associated with SI after 1 year. Significant interactive effects were detected between sTNFα (higher) levels and the −850 C/T (C/C or C/T) polymorphism on SI 2 weeks after ACS and between the two (−850 CC or CT and −308 G/A or AA) polymorphisms on SI 1 year after ACS. Conclusions: The sTNFα level and two polymorphisms (−850C/T or −308 G/A), separately or in combination, could be time-specific biomarkers for SI in ACS. Focused interventions for ACS patients at risk of SI might reduce the suicidal burden in patients with ACS.